Determinants of Customer’s Intention to Use Murabaha Financing In Indonesia: Modified the TRA Model - Dety Nurfadilah; Sudarmawan Samidi (Institute for Research and Community Empowerment (LPPM TAZKIA), 2019)
This study aims to investigate factors influencing customer’s intention to use murabaha financing in Indonesia, and to what extent do attitude, social influence, religious obligation, price mechanism, and government support affect customer’s intention to use murabaha financing in Indonesian Islamic banks. 200 customers of Bank Muamalat Indonesia and Bank Syariah Mandiri were collected through a semi-structured questionnaire. The study modifies the theory of reasoned action and extends the earlier research conducted by Amin et al. (2011) and Ali et al. (2015). The findings show that attitude, social influence, government support, and price mechanism have a positive and strong relationship with intention to use murabaha financing. In the contrary, the religious obligation is not the main factors that determine the customer’s intention to use murabaha financing. The findings have practical implications to fill the gap between the current practices of Islamic banks and perception from a consumer point of view. This study also analyzed possible variables that may influence the strategies to attract more customers to use murabaha financing and increase Islamic bank’s market share. To the best of author’s knowledge, this is the first study which modified the TRA model in the context of murabaha financing in Indonesian Islamic Banks.